2015
DOI: 10.1631/jzus.b1400219
|View full text |Cite
|
Sign up to set email alerts
|

CRP, but not TNF-α or IL-6, decreases after weight loss in patients with morbid obesity exposed to intensive weight reduction and balneological treatment

Abstract: Abstract:Objective: The aim of this study was to evaluate the concentrations of C-reactive protein (CRP), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and the degree of homeostasis model assessment-insulin resistance (HOMA-IR) in patients with morbid obesity exposed to a three-week low-calorie diet and balneotherapy. Methods: The study included 33 patients (25 females and 8 males; mean age 46 years) with body mass index (BMI) values of >40 kg/m 2 . Evaluations of CRP, IL-6, TNF-α, lipid profile, HOMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Another study showed an improvement of the inflammatory profile of obese patients who consumed a low-calorie diet and had a weight loss of 9% after 21 days, but it did show any important decrease in TNF-α [ 44 ]. Additionally, the authors suggested removing fatty tissue to reach a better result of TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed an improvement of the inflammatory profile of obese patients who consumed a low-calorie diet and had a weight loss of 9% after 21 days, but it did show any important decrease in TNF-α [ 44 ]. Additionally, the authors suggested removing fatty tissue to reach a better result of TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a major factor associated with elevated CRP in individuals with the metabolic syndrome [30], and CRP decreases after weight loss in obese subjects [31]. Harborne et al .…”
Section: Discussionmentioning
confidence: 99%
“…Circulating concentrations of CRP, TNF-α, and IL-6 are generally elevated in participants with insulin resistance and obesity (18)(19)(20). Weight loss has been shown to decrease concentrations of these proinflammatory factors and improve insulin sensitivity (21)(22)(23). Very few studies have examined the impact of intermittent fasting versus daily CR on inflammatory mediators (5,7,8).…”
Section: Wwwobesityjournalorgmentioning
confidence: 99%